The effect of educational intervention on lifestyle modification associated with osteoporosis in female students - Farangis Sharifi; Nader Sharifi (Mashhad University of Medical Sciences, 2017)
Introduction: Osteoporosis is a chronic, progressive skeletal disease associated with high health cost for the treatment of respective complications, follow-up care, and rehabilitation. Lifestyle plays a critical role in the prevention of the diseases, especially during adolescence and early adulthood. The aim of this study was to determine the effect of educational intervention on lifestyle modification associated with osteoporosis in female students of Islamic Azad University, Kazerun Branch. Materials and methods: This pre-and post- controlled semi experimental study was carried from October to February 1395, on 136 female students of Islamic Azad University randomly selected using multistage sampling method (68 students for each of intervention and control groups). To collect data in this study, two questionnaires including demographic questionnaire related to demographic and socioeconomic status and Walker standard lifestyle questionnaire for measure of health promotion behaviors including six areas of nutrition, exercise, health responsibility, stress management, interpersonal support and self-actualization were used and before the intervention, immediately and 2 months after the intervention were given to the participants. Data were analyzed using student t-test, Chi-square and repeated measures variance analysis using SPSS software (version 24). P value less than 0.05 was considered significant. Results: Analysis of variance in repeated measures showed that the mean score of lifestyle questionnaire in total of p Conclusion: Educational intervention is effective in improving preventive life style of osteoporosis.